The embedded librarianship in scholarship and research among academic librarians in the Malaysian research universities / Khasiah Zakaria - Zakaria, Khasiah (2015)
This study investigates the concept of the embedded librarianship in relation to scholarship and research support. This study started with the aim of investigating the perception of academic librarianship in scholarship roles, attitude towards research and knowledge production. However an embedded librarianship in support of scholarship and research emerged. Embedded librarianship in this study refers to a situation where librarians embedded programme in training users, provide ready reference, perform in-depth topical research, and involve in library resource development. The population of the study comprises the academic librarians from five Malaysian researcher universities. This quantitative method of study used questionnaire as the instrument to collect data. Eighty nine items from three variables formed the basis of a survey instrument using a seven point interval scale. The instrument was distributed to the two hundred twenty academic librarians working in the five Malaysian research universities. A total of one hundred and thirty nine (59%) respondents returned the questionnaire. A combination of descriptive statistics, means ranking, one-way analysis of variance (ANOVA), independent-samples t test, regression and Pearson's Product Moment Correlations were used in this study using the SPSS version 19.0. The findings revealed that the level of scholarship roles among academic librarians is quite high, particularly in the teaching of information literacy such as accessing and using information. Academic librarians are involved in research support activities but only at a moderate level. The involvement in publishing support activities is lowest compared to the other variables of the scholarship roles, such as teaching of information literacy, publishing support activities and information consultancy. Academic librarians have positive attitude towards research particularly those that can benefit library users. The academic librarians have low research anxiety, implying that they are comfortable with the various aspects of research. With respect to knowledge production they acknowledge their support on research related with library service fields. Furthermore, there is no evident o f significant relationship between the overall level of scholarship roles of librarians and the levels of support on knowledge production (r = 0.119; p - 0.179 > 0.05). There is a positive moderate correlation between attitude towards research with knowledge production(r = 0.550; p < 0.01). Scholarship roles (r = 0.376, p<0.01) as a whole is positively but rather weakly correlated with attitude towards research (r = 0.350; p < 0.01). However, there are differences in terms of perception about scholarship roles, attitude towards research as well as knowledge production in regard with designation, age and education, working experience and salary grades. The findings will be useful for curriculum planners involved in managing the development of librarian’s competencies and training of information professionals in the Faculties and Departments of Library and Information Science, librarians at all levels and industries, and students who aspire to work in the library or information science organisations.